Passive versus Active Fund Performance: Do Index Funds Have Skill? - Crane, Alan D.; Crotty, Kevin (Journal of Financial and Quantitative Analysis, 2018)
We apply methods designed to measure mutual fund skill to a cross section of funds that is unlikely to exhibit managerial portfolio selection skill: index funds. Surprisingly, these tests imply index fund skill exists, is persistent, and is in similar proportion as in active funds. We use the distribution of passive fund performance to gauge the incremental ability of active managers. Outperformance by top active funds is lower when benchmarked to the index fund distribution and disappears when we account for residual risk. Stochastic dominance tests suggest no risk-averse investor should choose a random active fund over a random index fund.